Dentine microhardness after different methods for detection and removal of carious dentine tissue - Mollica, Fernanda Brandão [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Gonçalves, Sergio Eduardo de Paiva [UNESP]; Mancini, Maria Nadir Gasparoto [UNESP] (FapUNIFESP (SciELO), 2012)
There are several methods for identifying carious dentinal tissue aiming to avoid removal of healthy dentinal tissue. ObjectiveS: The purpose of this study was to test different methods for the detection of carious dentinal tissue regarding the amount of carious tissue removed and the remaining dentin microhardness after caries removal. Material and Methods: The dentin surfaces of 20 bovine teeth were exposed and half of the surface was protected with nail polish. Cariogenic challenge was performed by immersion in a demineralizing solution for 14 days. After transverse cross-section of the crown, the specimens were divided into four groups (n=10), according to the method used to identify and remove the carious tissue: Papacárie, Caries-detector dye, DIAGNOdent and Tactile method. After caries removal, the cross-sectional surface was included in acrylic resin and polished. In a microhardness tester, the removed dentin thickness and the Vickers microhardness of the following regions were evaluated: remaining dentin after caries removal and superficial and deep healthy dentin. Results: ANOVA and Tukey's test (α=0.05) were performed, except for DIAGNOdent, which did not detect the presence of caries. Results for removed dentin thickness were: Papacárie (424.7±105.0; a), Caries-detector dye (370.5±78.3; ab), Tactile method (322.8±51.5; bc). Results for the remaining dentin microhardness were: Papacárie (42.2±10.5; bc), Caries-detector dye (44.6±11.8; abc), Tactile method (24.3±9.0; d). ConclusionS: DIAGNOdent did not detect the presence of carious tissue; Tactile method and Papacárie resulted in the least and the most dentinal thickness removal, respectively; Tactile method differed significantly from Papacárie and Caries-detector dye in terms of the remaining dentin microhardness, and Tactile method was the one which presented the lowest microhardness values.
Keywords: Dental caries; Dentin; Hardness; Lasers